2022
DOI: 10.3390/vaccines10071106
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Kidney and Heart Function Bioindicators and the Expressions of Toll-Like, ACE2, and NRP-1 Receptors in COVID-19

Abstract: Background: COVID-19 impacts the cardiovascular system resulting in myocardial damage, and also affects the kidneys leading to renal dysfunction. This effect is mostly through the binding with angiotensin-converting enzyme 2 (ACE2) and Neuropilin-1 (NRP-l) receptors. Toll-Like Receptors (TLRs) typically combine with microbial pathogens and provoke an inflammatory response. Aim: This work aims to compare the changes in kidney and heart function bioindicators and expressions of TLRs (TLR2 and TLR2) as well as AC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Upregulated NRP-1 is related to deterioration of renal function. This was verified by the significant correlation between NRP-1 expression and serum creatinine and urea levels in severe COVID-19 patients ( 32 , 77 ). The consumption of NRP-1 after infection may lead to impaired podocyte function and aggravate DKD ( 78 ).…”
Section: Dkd and Covid-19mentioning
confidence: 63%
See 1 more Smart Citation
“…Upregulated NRP-1 is related to deterioration of renal function. This was verified by the significant correlation between NRP-1 expression and serum creatinine and urea levels in severe COVID-19 patients ( 32 , 77 ). The consumption of NRP-1 after infection may lead to impaired podocyte function and aggravate DKD ( 78 ).…”
Section: Dkd and Covid-19mentioning
confidence: 63%
“…Sultan et al. reported that both expressions of TLR2, TLR4 mRNA, and NRP-1 were elevated in moderate and severe COVID-19 patients, and the NRP-1 level was positively correlated with TLR2 and TLR4 ( 77 ). Upregulated NRP-1 is related to deterioration of renal function.…”
Section: Dkd and Covid-19mentioning
confidence: 99%
“…In addition, the clinical symptoms of COVID-19 infection were confirmed by the Physician. The confirmed COVID-19 patients were categorized into two groups, moderate and severe, according to the guidelines for diagnosis and management of COVID-19 released by National Health Commission of China [ 25 ] and also according to our previous publications [ 14 , 15 ]. Patients in the group had symptoms such as fever and respiratory tract symptoms and pneumonia manifestation, which were seen in imaging.…”
Section: Methodsmentioning
confidence: 99%
“…NRP-1 is implicated in several aspects of a SARS-CoV-2 infection, including possible spread through the olfactory bulb and into the central nervous system (CNS) and increased NRP-1 RNA expression in lungs of severe COVID-19 [ 13 ]. Recently, it was found that impairment of renal and cardiac function biomarkers in serum might be the result of a cytokine storm and an increase in the expression of ACE-2 and NRP-1 in COVID-19 patients [ 14 , 15 ]. Understanding how SARS-CoV-2 enters and spreads throughout human organs is important for developing preventative and therapy measures.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 patients were split into two groups in accordance with the seventh edition of the Guidelines on the Diagnosis and Cure of COVID-19 published by the National Health Commission of China [ 10 ] and according our previous publications [ 9 , 11 , 12 ]. Thus, the study population include three groups (each of 50 individuals), which are healthy control, moderate COVID-19 and severe COVID-19 groups.…”
Section: Methodsmentioning
confidence: 99%